P(x)=-6x-9

Simple and best practice solution for P(x)=-6x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P(x)=-6x-9 equation:



(P)=-6P-9
We move all terms to the left:
(P)-(-6P-9)=0
We get rid of parentheses
P+6P+9=0
We add all the numbers together, and all the variables
7P+9=0
We move all terms containing P to the left, all other terms to the right
7P=-9
P=-9/7
P=-1+2/7

See similar equations:

| 5x+3x=2+5 | | 7x−9=4x | | 43+8p=p+21 | | 2x+45=87 | | 13+2a=3a-14+24 | | 14v+50=2(5v+29) | | 420(2r+10=) | | -w+66=2w | | 8x=x2+15 | | n4+5=17 | | y2-144=0 | | 4-3t=6t-8 | | 3x-9-3=2x+14 | | Y=6E-06x | | 18c–25=38 | | 4(n+5)=17 | | -5(x+2)+16=15-6x | | −5(x+2)+16=15−6x | | 2d−6=2 | | 3x+(4x+13)=125 | | 0.4(2x+1/2)=3(0.2+(-2))-4 | | 3x-10=2x+14 | | 15y+18=-6y+10 | | x+2x+2x+3=31 | | 8-r=2 | | 55+2x=121 | | 60/m+m=5 | | 6w-12-3w+11=5 | | 34=-8x+4x | | 10–3x–5x+12=–x+1 | | 10x+16x=26x | | 7^(6x-2)=41 |

Equations solver categories